WOMEN’S BELIEFS REGARDING FOOD RESTRICTIONS DURING COMMON CHILDHOOD ILLNESSES: A HOSPITAL BASED STUDY - Ali, Niloufer Sultan; Azam, Syed Iqbal; Noor, Rahat (Journal of Ayub Medical College Abbottabad, 2003)
Background: Malnutrition continues to be a major problem in Pakistan. Inadequate nutrition contributes substantially to childhood death and disease. Restriction of diet during common childhood illnesses further compromises the nutritional status of the child. The present study aims to determine the beliefs and practices regarding food restrictions during common childhood illnesses. Methods: A cross-sectional survey was conducted at Community Health Centre (CHC), of The Aga Khan University Hospital, Karachi to understand the beliefs and practices regarding food restrictions in common childhood illnesses. Four hundred adult females were interviewed from July-September 2000. A self-administered questionnaire was filled by the respondent. Results: Major sources of information about restriction of various foods during different illnesses were relatives. Sixty five percent of the respondents believed that heavy food should be restricted during diarrhoea and oily food during jaundice. Sixty six percent of the respondents believed that cold food should be restricted during cold/cough and twenty three percent believed that oily food should be restricted during typhoid. Conclusion: Beliefs’ regarding food restrictions during illnesses plays a very important role on the nutrition status. Surprisingly, medical doctors and other health care givers were also the source of information for advising food restrictions in certain childhood illnesses. Therefore there is a need for educating the physicians and other health care workers along with the mothers about food concepts and feeding practices during health and diseases. Protein energy malnutrition can be reduced to some extent if wrong dietary beliefs about child feeding practices in a community can be removed with health education programme. Key Words: Food habits; food; cultural characteristics.